If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(5x + 4) = 156 Reorder the terms: -6(4 + 5x) = 156 (4 * -6 + 5x * -6) = 156 (-24 + -30x) = 156 Solving -24 + -30x = 156 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -30x = 156 + 24 Combine like terms: -24 + 24 = 0 0 + -30x = 156 + 24 -30x = 156 + 24 Combine like terms: 156 + 24 = 180 -30x = 180 Divide each side by '-30'. x = -6 Simplifying x = -6
| 3x+5+7x-4+3x+5+7x-4=102 | | 5x+16=9x-8 | | Log(4x+14)=3 | | 2b-3=37 | | (X+y)(x-y)=0 | | -5-2(3+6r)=-71 | | 7n^2-3=39 | | 4+6x=-1+x | | 3(2y-2)y=5 | | 2x=7.1 | | q^2=-5 | | 5x+72y=1 | | 0=48x-.6x^2 | | y=3a+b | | 6x-50=2x+10 | | -4+6(-5k-6)=-130 | | 22x+9=25x | | 7-6n=55 | | 2x-4x-10=-20 | | 0=48t-.6t^2 | | 12n-4=12n-4 | | X(x+8)=8 | | [x-6]+18=41 | | 5x+2=10x-38 | | -0.68+1.7r=3.57 | | -5(-1-5b)=155 | | r^2-2v-48=0 | | 7x+9-5x=-11 | | C=KNYsolvey | | -0.68+1.7=3.57 | | 480=48x-.6x^2 | | 4y-3-6y= |